Strengthening Religious Moderation Values through Islamic Education in the Digital Disruption Era - Aswar Rahmat (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: Strengthening Religious Moderation Values through Islamic Education in the Era of Digital DisruptionObjective: This study aims to describe and analyse strategies for strengthening moderate religious values through Islamic education at SD Negeri 43 Seluma in the digital disruption era. Method: The research method is a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Data analysis was conducted through data reduction, presentation, and conclusion drawing. Results: Islamic education teachers apply contextual and integrative teaching strategies that link the teaching materials to social realities and the challenges of the digital era. The use of digital media such as videos, interactive materials, and online discussions enhances student engagement in learning while also serving as a tool for internalizing values of tolerance, appreciating differences, and open-mindedness. Challenges include limited digital infrastructure, varying digital literacy among students, and the risk of exposure to negative content. Conclusion: This study concludes that technology-based adaptive education can effectively promote religious moderation from an early age. Contribution: This study strengthens students' digital literacy and encourages active collaboration between schools, families, and communities to support moderate and relevant Islamic education in line with contemporary developmentsINDONESIAN: Penguatan Nilai Moderasi Beragama melalui Pembelajaran PAI di Era Disrupsi DigitalTujuan: Studi ini bertujuan untuk menggambarkan dan menganalisis strategi penguatan nilai-nilai moderasi agama melalui pendidikan Islam di SD Negeri 43 Seluma pada era disrupsi digital. Metode: Metode penelitian yang digunakan adalah pendekatan kualitatif deskriptif dengan teknik pengumpulan data meliputi observasi, wawancara, dan dokumentasi. Analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil: Guru pendidikan Islam menerapkan strategi pengajaran kontekstual dan integratif yang menghubungkan materi pembelajaran dengan realitas sosial dan tantangan era digital. Penggunaan media digital seperti video, materi interaktif, dan diskusi online meningkatkan keterlibatan siswa dalam proses belajar sambil juga berfungsi sebagai alat untuk menanamkan nilai-nilai toleransi, menghargai perbedaan, dan keterbukaan pikiran. Tantangan meliputi infrastruktur digital yang terbatas, tingkat literasi digital yang bervariasi di kalangan siswa, dan risiko paparan terhadap konten negatif. Kesimpulan: Penelitian ini menyimpulkan bahwa pendidikan adaptif berbasis teknologi dapat menjadi alat yang efektif dalam mempromosikan moderasi agama sejak usia dini. Kontribusi: Penelitian ini berkontribusi sebagai penguatan literasi digital siswa dan mendorong kolaborasi aktif antara sekolah, keluarga, dan masyarakat untuk mendukung pendidikan Islam yang moderat dan relevan dengan perkembangan kontemporer.